IMPACT OF ECO-FRIENDLY SOIL MICROBE ON MACROTYLOMA UNIFLORUM (LAM.) VERDC: A MEDICINAL PULSE.: Life Sciences-Plant Sciences - SHASHI KANT SHUKLA; RAJESH KUMAR; ASHUTOSH PATHAK; MADHU PANDEY; AFIFA QIDWAI; MANISHA PANDEY; ANUPAM DIKSHIT (International Journal of Life Science and Pharma Research, 2022)
The present study was done with the chief objective of enhancing the cultivation and growth of Macrotyloma uniflorum, (Lam.) Verdc. a medicinal pulse belongs to fabaceae and one of the chief source important proteins. The whole experiment was done in the light of macro and micronutrients analysis of for pot experiment. Potassium (K) was found in greater amount whereas phosphorous (P) was found as a limiting factor than their recommended value. So, Paenibacillus polymyxa was selected to dissolve the nutrients into their organic form. The results were observed in 0, 10 and 25 days, reflected in comparison to control, treatments with used plant growth promoting bacterium (PGPB) ultimately increases root, shoot, total lengths and no. of leaves in plant. Moreover, such improved results have been found in the measurement taken after 10 days and these more enhancement after 25 days respectively. Furthermore, it can be concluded that use of P. Polymyxa can enhance growth and development of M. uniflorum to meet the current demands.